A influência da l-glutamina como imunofármaconutriente na resposta imunometabólica em HIV/AIDS : estudo piloto - Leones, Juliana Ramos (2016)
The deterioration of the immune system caused by the human immunodeficiency virus (HIV) leads to nutritional and metabolic disorders. The use of antiretroviral therapy becomes important but insufficient in the face of changes suffered by these patients. Thus, the search for a drug that has nutritional action and stimulates the immune response of this patient is important. Glutamine has been reported with these properties, but a very limited extent in patients living with HIV / AIDS. Objective: To evaluate the influence of glutamine, administered orally in patients living with HIV / AIDS receiving prolonged treatment (02 years) with antiretroviral zidovudine / lamivudine and lopinavir / ritonavir. Methods: Prospective, randomized clinical trial conducted in patients with HIV / AIDS and make outpatient treatment at a specialized unit in the city of Cuiaba- MT, between July and December 2014 were included in the adult patient study of both sexes, between 18 and 50 years old, HIV positive, registered to the unit in regular treatment and antiretroviral (zidovudine / lamivudine and lopinavir / ritonavir) for at least two years, with Class A Subjective Global Assessment (SGA A = good nourished), which agreed to participate with the signing of the Informed Consent (IC). Randomization was performed via the draw through envelope containing a sequence number in ascending order. Patients with even numbers contemplated belonged to the group A and the group B.Os odd numbers belonging to group A patients received 0.5 mg / kg / day of glutamine powder packed in sachets with maximum dose 30 g each. The B group received maltodextrin (0.5 mg / kg / day) powder (unflavored), also packaged in sachets with a maximum dose of 30 g each. For statistical analysis, we used the Levene test. To ensure the normality of the data performed the Kolmogorov-Smirnov test. Like all variables were considered homogeneous and there was distribution of normality in the above tests (p> 0.05), we used the Student t test for paired comparison of the two groups. To analyze the results of laboratory tests in the first and eighth day, we used ANOVA (Two-Factor with repetition). Results: The evaluated demographics were similar between the two groups. The biochemical variables related to the metabolic response of patients with HIV / AIDS were conducted in the first (T0) and eighth day (T8) of the study, before the start of supplementation or glutamine or maltodextrin. All patients were classified as well- nourished (SGA A) according to the Subjective Global Assessment. Weight Average identical in both groups (p = 0.093). As for metabolic evaluation was statistically significant difference in the basal insulin dose in the group receiving glutamine (7.1 ± 2.7 vs 4.8 ± 2.0; p = 0.023). For CD4 + measures (p = 0.832) and CD8 + (p = 0.974) in both groups were not statistically significant. Conclusion: Based on these results we conclude that the use of glutamine improves metabolic responses, as assessed by measurement of basal insulin.